2010
DOI: 10.1371/journal.pone.0013127
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Ageing Eyes: Diverse Sites of Amyloid Beta Accumulation in the Ageing Mouse Retina and the Up-Regulation of Macrophages

Abstract: BackgroundAmyloid beta (Aβ) accumulates in the ageing central nervous system and is associated with a number of age-related diseases, including age-related macular degeneration (AMD) in the eye. AMD is characterised by accumulation of extracellular deposits called drusen in which Aβ is a key constituent. Aβ activates the complement cascade and its deposition is associated with activated macrophages. So far, little is known about the quantitative measurements of Aβ accumulation and definitions of its relative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 56 publications
7
72
1
Order By: Relevance
“…The presence of these cells may be indicative of an attempt to clear Aβ, but it has also been suggested that they may be accomplices in the development of AMD. 98 Recently, we showed that Aβ 1-42 accumulates with age in the OXYS retina, but its level is not elevated at the early stages of retinopathy (age 3 mo, Fig. 5).…”
mentioning
confidence: 87%
“…The presence of these cells may be indicative of an attempt to clear Aβ, but it has also been suggested that they may be accomplices in the development of AMD. 98 Recently, we showed that Aβ 1-42 accumulates with age in the OXYS retina, but its level is not elevated at the early stages of retinopathy (age 3 mo, Fig. 5).…”
mentioning
confidence: 87%
“…These cell classes also express β-secretase and are capable of producing Aβ (for review, see Ratnayaka et al, 2015). In genetically modified mice that have abnormalities in APP processing, Aβ accumulates sporadically within the RGC (Dutescu et al, 2009; Du et al, 2015), in the plexiform layers (Perez et al, 2009), in the nuclear layers (Shimazawa et al, 2008), in blood vessel walls (Liu et al, 2009), Bruch's membrane, outer segments of photoreceptors (Hoh et al, 2010) and within the retinal pigment epithelium (Park et al, 2014). In humans, Hoh et al (2010) also reported that Aβ accumulated in photoreceptor outer segments in post-mortem retina of AD patients.…”
Section: Retinal Biomarkersmentioning
confidence: 99%
“…Deposition of Aβ is common in disease (Weller et al, 1998;Armstrong, 2012;Mendal et al, 2013), but is also a feature of retinal ageing (Hoh Kam et al, 2010;Hoh Kam et al, 2013). Aβ deposition in brain vasculature causes endothelium dependent vasoconstriction (Thomas et al 1996;Townsend et al 2002;Niwa et al2000).…”
Section: Discussionmentioning
confidence: 99%
“…3 (Johnson et al, 2002;Lundh von Leithner et al, 2009;Hoh Kam et al, 2010;Hoh Kam et al, 2013). BM is part of the outer retinal blood barrier and deposition here is likely to alter outer retinal perfusion arising from the choroid.…”
Section: Submitted As a Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation